Han Mengyun on Gayatri Chakravorty Spivak. (ArtAsiaPacific)
The article explores the concepts presented by comparative literature scholar Gayatri Chakravorty Spivak in her work "Can the Subaltern Speak?". It discusses the silencing of subaltern women and the need for translation and representation to address their absence in cultural discourse. The author reflects on their own experience as a female artist from China and emphasizes the importance of honoring agency, promoting diversity, and telling women's stories.